The Role of Modular Education in the Development of Professional Competencies of Applied Bachelor Students - Sanina S.P (Moscow State University of Psychology and Education, 2018)
The modular principle of the educational process organization is considered in which practical work, training and introductory, educational practice, SSRP are included into the module, along with the theoretical content. The aim of the article is to consider possibilities of modular education in developing professional competencies of future primary school teachers. In the article experience of the module section approbation "Organization of students' learning activities at Arts and crafts lessons" is presented. Two models of the teacher's activity in the teaching process are described: the "instruction" model of the teaching process and the teacher's "controlling" activity. Experience of implementing the model of modular education at all stages is presented: an example of the task for students for educational and introductory practice is given; examples of questions discussed in reflexive work are given; how classroom studies are conducted taking into account the specificity of the subject "Arts and crafts". Examples of a test task and a case for the midterm assessment of students are provided. The effectiveness of the modular organization of the educational process in developing students' professional competencies of applied bachelor degree course is shown.